Synthesis and anticancer evaluation of spermatinamine analogues. Issue 6 (15th March 2016) - Moosa, Basem A.; Sagar, Sunil; Li, Song; Esau, Luke; Kaur, Mandeep; Khashab, Niveen M.
Graphical abstract: Abstract: Spermatinamine was isolated from an Australian marine sponge, Pseudoceratina sp. as an inhibitor of isoprenylcysteine carboxyl methyltransferase (Icmt), an attractive and novel anticancer target. Herein, we report the synthesis of spermatinamine analogues and their cytotoxic evaluation against three human cancer cell lines, that is, cervix adenocarcinoma (HeLa), breast adenocarcinoma (MCF-7), and prostate carcinoma (DU145). Analogues12, 14 and15 were found to be the most potent against one or more cell lines with the IC50 values in the range of 5–10 μM. The obtained results suggested that longer polyamine linker along with aromatic oxime substitution provided the most potent analogue compounds against cancer cell lines.